1977
DOI: 10.1002/cne.901710304
|View full text |Cite
|
Sign up to set email alerts
|

Aging of the rat olfactory bulb: Growth and atrophy of constituent layers and changes in size and number of mitral cells

Abstract: A quantitative study of the rat olfactory bulb during aging was carried out by directly measuring or calculating the following parameters at 3, 12, 24, 27, and 30 months: The volume of the glomerular, external plexiform, and internal granular layers, a relative measure of the size of the olfactory nerve layer, the mean volume of mitral cell nuclei and perikarya, a relative measure of the mean volume of the mitral cell dendritic tree as well as the total length and mean cross-sectional area of its constituent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
79
2

Year Published

1978
1978
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(92 citation statements)
references
References 50 publications
11
79
2
Order By: Relevance
“…Contrary to earlier reports of extensive volume and cell losses in the aging brain, our data suggest more subtle region-and layer-specific changes (1, 2). In the OB, there are reports of both strain-and species-dependent effects of aging (14)(15)(16)(17). Our results, which included more intermediate time points, establish that OB volume is stable from 2 mo onward in C57BL/6J mice.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Contrary to earlier reports of extensive volume and cell losses in the aging brain, our data suggest more subtle region-and layer-specific changes (1, 2). In the OB, there are reports of both strain-and species-dependent effects of aging (14)(15)(16)(17). Our results, which included more intermediate time points, establish that OB volume is stable from 2 mo onward in C57BL/6J mice.…”
Section: Discussionsupporting
confidence: 70%
“…Some agerelated changes in the OE and OB were reported, mainly in rats (4,(14)(15)(16)(17)(18)(19)(20), but none document the kinetics of the defects. Here, we report quantitative morphometric analyses of the aging mouse OB at 2, 6, 12, 18, and 24 mo, focusing on changes in layer morphology, neuronal populations, synaptic circuitry, and OR map.…”
mentioning
confidence: 99%
“…From four to eighteen months of age, sexually mature albino mice have significant decreases in VRN nuclear density and total VRN numbers per VNO (Wilson & Raisman, 1980). Age-related reduction is also well documented for structures of the main olfactory system in humans (Bhatnagar et al, 1987;Meisami et al, 1998) and mice (Hinds & McNelly, 1977). More notably, a recent study on captive mouse lemurs (Microcebus murinus), revealed an age-related decline in the olfactory abilities as well as endocrine responses of males to female urine (Aujard & Nemoz-Bertholet, 2004), a phenomenon for which VNNE deficits may also play a role.…”
Section: Discussionmentioning
confidence: 84%
“…Thus the somatic hypertrophy observed in this study from the 24th month onward could be explained as a compensatory mechanism to maintain the same total somatic volume in spite of the increase in the total volume in the dLGN. This, according to Hinds and McNelly (1977), Flood et al, (1985), and Coleman and Flood (1986), could be related to an increase in the dendritic tree in order to maintain the existing synaptic connections, despite the increase in the dLGN total volume, or perhaps, to compensate for the decrease in the number of synapses and/or in their efficiency during aging (Ahmad and Spear, 1993).…”
Section: Discussionmentioning
confidence: 99%